ANALYSIS OF THE FREEMASONS IN THE LIGHT OF "THE COMPLETE WORKS OF MARX AND ENGELS". (1st April 2012) - Unknown
Abstract : Studies of the Freemasons, even though rare and scattered, have been carried out by Chinese scholars for a long time, but they have never become the focus of academic debates until recent years. There are dozens of discussions concerning the Freemasons in The Complete Works of Marx and Engels, a legacy too precious to be overlooked. This article tries to summarize and analyze the significance of the Freemasons in the context of Marx and Engels through a careful textual study using the Complete Works. Finally, some conclusions and heuristics regarding a Marxist understanding of the Freemasons are presented.